DECLARATIVE SENTENCES AS EMOTIONAL NARRATIVES - Fitra, Muh. Al Fachrizah; Sari, Ulvah; Qalbi, Chairunnisa Nurul (Universitas Muhammadiyah Lampung, 2025)
This study analyzes the function of declarative sentences in constructing emotional narratives within the lyrics of